Membangun Hubungan Indutrial Dalam Mencapai Keharmonisan Antara Pegawai Dengan Manajemen Di CV SWADAYA TEKSTIL - Resya Dwi Marselina; Herdiana Nugraha; Dikdik Jamalludin; Ririn Trisafitri; Warda Anisa Maharani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to explore and analyze efforts to build harmonious industrial relations in the CV Swadaya Tekstil work environment. The main focus of this research is to find out 1) What influences harmony in CV. Swadaya Textiles? 2) What is the role of leadership in building harmonious industrial relations at CV. Swadaya Textile?. This research was carried out directly by conducting interviews with one of the CV Swadaya textile parties to gain an in-depth understanding of the dynamics of industrial relations in this textile company. The results of this research are key factors that contribute to harmony in industrial relations, including open communication that allows effective exchange of information between employees and employers, active employee participation in the decision-making process, and fairness in the implementation of company policies.